Funding Higher Education in Uganda in an Era of Growth - Nannyonjo, Harriet; Najjumba Mulindwa, Innocent; Usher, Alex (World Bank, Washington, DC, 2013)
This note presents a review of the system of funding higher education in Uganda and provides government and stakeholders with some options for meeting the twin goals of increasing participation and quality in higher education, especially in science-related disciplines. Part I provides an overview of the current situation of Ugandan higher education. It begins with a brief review of the country s recent social and political history and continues on to describe the historical development and current situation of the country s higher education system. The final section provides an overview of the current state of debate about the way forward in improving financing of higher education in Uganda. In part II, possible solutions are outlined. The Government of Uganda has two broad policy goals for higher education. The first is to increase the number of graduates, especially in the areas of science and technology. The second is to expand access to universities to a broader selection of the Ugandan population, allowing those of lower socio-economic status to benefit as much as possible from higher education. Policies to achieve both of these goals are presented in Part II.